Aplicação de Meta-modelos à Monetização de Jogos Free-to-Play - OLIVEIRA, Ruy Guilherme Silva Gomes de (2017)
The recent emergence of Free-to-Play games, also known as Freemium games, has considerably changed the way games are made. The definition of monetization strategies is now part of the process of making games. Choosing which strategy to adopt among the various ones and understanding how they work could be an arduous task. When analysing the market, to realize that popular games use similar strategies is not difficult, which demonstrates that the reuse of strategies is common among developers. Although there are catalogs of popular monetization strategies used by Free-to-Play games in the literature, little attention has been given to formalize the description of those strategies, leaving openings for misunderstandings and making the reuse harder. For that reason, a meta-model of Free-to-Play games monetization that allows the representation of Free-toPlay games monetization strategies based on a set of popular strategies is proposed. That meta-model, called Meta-F2P, was elaborated from the investigation of the most rentable Free-to-Play games for mobile devices. Besides that, case studies were used to validate and refine the accuracy, expressiveness and extensibility of that meta-model. Based on the results obtained, the applicability of the meta-model in the process of making games and the advantages and disadvantages of the use of case studies in the concept of meta-models are analyzed.